Stages of a Comprehensive Approach to Case Management for Patients with Hypertension and Cervical Root Syndrome with Risk Factors of Sedentary Lifestyle and Ergonomically Unfavorable Work Patterns - Rusnianah, Farida; RM, Fauziyyah (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2024)
Family physicians as gatekeepers in primary healthcare facilities must manage patients in a holistic and comprehensive manner, with a patient-centered approach. This case study focuses on a 61-year-old male patient with hypertension and cervical root syndrome, with risk factors including a sedentary lifestyle and ergonomically unfavorable work patterns. This report aims to provide an overview of patient management that considers not only the biological aspects but also the psychological and social dimensions. Patient-centered management is expected to reconcile the patient's perspective and spirit regarding the illness. This approach is crucial for family physicians to not only consider the disease diagnosis but also collaboratively work with the patient towards achieving management goals in line with their expectations.